2017
DOI: 10.1075/btl.129.07pol
|View full text |Cite
|
Sign up to set email alerts
|

Issues of terminology in public service interpreting

Abstract: This chapter focuses on interpreter-mediated institutional encounters and specialist language. Based on Niska’s (1998a; 1998b) and Valero-Garcés’(2005) taxonomies of strategies for translating specialist terminology, the author analyses instances of specialist language in a corpus of recordings of institutional encounters, and discusses which strategies are used by the interpreters to render specialist terms. The data were collected between 2007 and 2009 as part of an interdisciplinary project called “Communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They can only deduce from the location what the encounter could entail as far terminology is concerned, which of course is not entirely predictable, because in a court hearing, for example, they could be confronted unexpectedly with very technical medical terminology. Contradictorily enough, we know from the history of interpreting that institutionalisation, academisation and professionalisation have been much slower for dialogue interpreting (Pöchhacker 2013(Pöchhacker , 2016, as confirmed in Pöllabauer's interesting chapter (Pöllabauer 2017). From the empirical study that discusses the strategies dialogue interpreters employ to render specialist terms, it indeed results that -mostly nonprofessional -interpreters tend to omit, simplify or paraphrase specialist vocabulary (Pöllabauer 2017: 152).…”
Section: Preparation: the Sign Language Interpreter's (Sli) And The D...mentioning
confidence: 96%
“…They can only deduce from the location what the encounter could entail as far terminology is concerned, which of course is not entirely predictable, because in a court hearing, for example, they could be confronted unexpectedly with very technical medical terminology. Contradictorily enough, we know from the history of interpreting that institutionalisation, academisation and professionalisation have been much slower for dialogue interpreting (Pöchhacker 2013(Pöchhacker , 2016, as confirmed in Pöllabauer's interesting chapter (Pöllabauer 2017). From the empirical study that discusses the strategies dialogue interpreters employ to render specialist terms, it indeed results that -mostly nonprofessional -interpreters tend to omit, simplify or paraphrase specialist vocabulary (Pöllabauer 2017: 152).…”
Section: Preparation: the Sign Language Interpreter's (Sli) And The D...mentioning
confidence: 96%
“…Medical interviews often abound with terminology, one of the main language barriers in institutional talk (see also Pöllabauer, 2017). Meyer (2006) reported that ad hoc interpreters in such cases tend to "de-terminologise" specific terms by paraphrasing them in plain language (p. 21; cited from Pöllabauer, 2017).…”
Section: Brokering Comprehensionmentioning
confidence: 99%
“…Medical interviews often abound with terminology, one of the main language barriers in institutional talk (see also Pöllabauer, 2017). Meyer (2006) reported that ad hoc interpreters in such cases tend to "de-terminologise" specific terms by paraphrasing them in plain language (p. 21; cited from Pöllabauer, 2017). Pöllabauer (2017) called such a practice "ad hoc terminology management" (p. 134), whereas, according to Angelelli (2004a), this practice indicates the interpreter's active efforts to broker comprehension and balance the distribution of power between doctor and patient.…”
Section: Brokering Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation